Design and Control Underwater Robot Based on Smartphone - Lamin Rene Loua; Dewi Lestari; Elvan Yuniarti; Rista ‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎ (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2023)
Underwater robot is a type of robot specially designed and configured to operate underwater, especially in seas, rivers, and lakes. The main purpose of underwater robots is to perform various tasks and missions underwater, which are often difficult or dangerous for humans to carry out. The method used to design the underwater robot is with a smartphone control system. The robot can move according to the user's commands by being connected through a internet network, allowing the robot and smartphone to be interconnected. This underwater robot is equipped with a camera and two lamps, and the images captured by the camera are displayed on a personal computer. Meanwhile, the lights are controlled by the user using a smartphone. The research results show that the underwater robot can be controlled to a depth of 0.5 meters with an average button press speed of 1 second in floating conditions and 2.9 seconds at a depth of 15 centimeters. The application of this robot can take photos, display good images, and monitor activities underwater. In addition, the captured image from underwater robot are also good and the image produced are clearly visible both on land and in the water.